Employees' skills in the Italian private sector: qualification, competences and task discretion - Passarelli, G (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2007)
The main aim of this paper is to contribute to the debate on New Forms of Management and their impact on the involvement of the workforce in the organisation. Broadly speaking, it could be described as the shift from an 'industrial relations' perspective to a 'human resource management' perspective. In particular this paper addresses - on the basis of an Organisation, Learning and Competences survey - the relationship between competence and organisational commitment among Italian private sector employees in several economic sectors and occupations. In order to analyse this relationship the paper uses principal component analysis, building some summary indicators for skills, task discretion and organisational commitment. The survey evidence shows a low correlation between skills development and organisational commitment. Therefore, the hypothesis of a virtuous cycle between new technological and organisational systems, high quality productive process and products, and development of skills and organisational commitment is not confirmed. Particularly, this cycle is not confirmed for professionals, personal services workers and advanced sectors. The article concludes with the hypothesis that high skilled employees are more attached to their jobs than to their organisations, confirming that job commitment does not always imply organisational commitment.